Pengaruh Budaya Organisasi, Struktur Organisasi, PemanfaatanTeknologi Informasi, dan SIA Terhadap Kinerja Karyawan pada Lembaga Perkreditan Desa Se- Kecamatan Abiansemal - Ni Putu Wulandari; Kadek Dewi Padnyawati (UNHI Press, 2022)
Employee performance is an importan element that the company pays attention to in order to achieve its goals. Seeing the importance of performance, the author would like to write a paper that contains the factors that cause performance improvement both from an organizational culture, the structure within a company, the benefits of using technology, or AIS. The LPD in Abiansemal sub-district has 33 active LPDs with 311 employees who make up the population. The sample was selected using a purpose sampling technique with the results of 132 respondents. Later observations will use regression techniques to manage the data. Observers find research results that reveal that performance is influenced by the culture that is applied and carried out in the organization. The organizational structure, the use of a technology, and SIA also participate in the factors that cause employee performance improvement.